Review on Yashad Bhasma – A Herbometallic Preparation of Indian System of Medicine: Review on Yashad Bhasma – A Herbometallic Preparation of Indian System of Medicine - Maheshwari, Surbhi (International Journal of Pharmaceutical & Biological Archive, 2021)
Rasa Shastra an ancient science of pharmaceutics that primarily utilize metals and minerals in the form of Bhasma for therapeutic purpose. Yashad Bhasma – a zinc-based herbometallic preparation is a well-known bhasma (based on single metal) for its wide range of utilization in the treatment of eye diseases, anemia, diabetes, asthma, skin diseases, etc. Rasaka Satva is found mentioned in Rasarnava for the first time. Zinc is first described in Madanpal Nighantu under the name Yashad but not described things related to Yashad Bhasma. In Rasa Grantha, Ayurveda Prakasha was the first to describe Yashad as a Dhatu among Seven Dhatus (metals) and also described other things related to Yashad Bhasma. The present work aimed to collected and analyzed various references of Yashad Bhasma from available classical text. Various published articles were also searched and included to review updated knowledge regarding the Yashad Bhasma.